Geomorphology of an Exhumed Carboniferous Paleosurface in the Southern Gaspé Peninsula, Québec: Paleoenvironmental and Tectonic Implications - Jutras, Pierre; Schroeder, Jacques (Géographie physique et Quaternaire, 1999)
AbstractCarboniferous sedimentation in the southern Gaspé Peninsula has fossilized a paleosurface which is now gradually being exhumed by erosion. Part of the surface was horizontally cut by a major peneplanation event that took place between 290 Ma (Permian) and 200 Ma (Jurassic). Exhumation of the surface below the peneplanation line must also have started by Jurassic time in response to the en bloc uplift of the evolving Atlantic Ocean's passive margins. Some geomorphic features of the exhumed paleosurface bring clues regarding Carboniferous paleoenvironments and tectonics. A planation surface limited by a scarp, which is leading to a higher planation surface occupied by the same rock formations, is here interpreted as a paleo- wave-cut platform (associated to the Windsor transgression) for it cannot be explained by differential erosion, fault movement or "etchplanation". A series of fault scarps cutting through planation surfaces are interpreted as being the result of post-Acadian fault activity. The preservation of limestone hogbacks on the exhumed paleosurface, which are interpreted as having evolved under an arid climate, is believed to be either related to a pre-Windsor clastic fossilization or to post-Windsor lateral displacement. The tightly embanked river system, which is still currently dissecting the Peninsula's main planation surface, and the karstic systems of both that surface and the exhumed paleosurface, are interpreted as having evolved since Jurassic Time, except for a few cases of river antecedence in the north-central highlands which are interpreted as representing even older river routes.